Seminal Attributes and Semen Cryo-banking of Nepalese Indigenous Achhami (Bos indicus) Bull under Ex-situ Conservation - Pankaj Kumar Jha; Saroj Sapkota; Neena Amatya Gorkhali; Bhoj Raj Pokharel; Ajeet Kumar Jha; Shishir Bhandari; Bhola Shankar Shrestha (The Korean Society of Animal Reproduction and Biotechnology, 2019)
The study was conducted to evaluate the seminal attributes and cryo-banking of Achhami (Bos indicus) bull semen. Of two Achhami bulls, 8 ejaculates from each bull were evaluated for seminal attributes. For semen freezing and cryo-banking, 4 ejaculates (having ≥2 mL semen volume, ≥75% of sperm motility and ≥1,000 × 106 cells/mL of sperm concentration) from each bull were used. Semen samples were diluted in egg-yolk-tris-citrate extender using a two-step dilution protocol, and were frozen in liquid nitrogen (LN2) vapour in a styrofoam box. The mean semen volume, colour, sperm mass activity, motility, viability, concentration, abnormal acrosome, midpiece and tail and, abnormal head of two Achhami bulls were 4.4 ± 0.5 mL vs. 2.5 ± 0.2 mL, 2.5 ± 0.1 vs. 2.4 ± 0.1, 3.5 ± 0.1 vs. 3.5 ± 0.1, 77.0 ± 1.1% vs. 78.3 ± 1.3%, 94.4 ± 0.5% vs. 91.0 ± 0.6%, 1137.7 ± 73.7 × 106 cells/mL vs. 1060.0 ± 44.3 × 106 cells/mL, 10.2 ± 0.5% vs. 10.3 ± 0.5% and 6.7 ± 0.5% vs. 8.2 ± 0.3%, respectively. The post-thawed sperm motility and viability were 53.0 ± 2.0% vs. 50.0 ± 0.0% and 80.2 ± 0.4% vs. 73.2 ± 0.7%, while evaluating by computer-assisted sperm analysis (CASA) system, the percentage of the progressive motility, fast motility, slow motility, local motility and immotile sperm were 75%, 68%, 7.4%, 16.6% and 8.6%, respectively. A total number of 620 doses semen straw were cryo-banked. Due to the acceptable post-thawed sperm motility and viability recorded, cryopreservation of Achhami semen is hereby recommended so as to preserve the Achhami breed. For further validation, the fertility will be observed from the produced frozen semen.